Advances in Mechanical and Energy Technology Select Proceedings of ICMET 2021 - Yadav, Sanjay; Jain, Prashant Kumar; Kankar, Pavan Kumar; Shrivastava, Yogesh (Lecture Notes in Mechanical Engineering, 2023)
This book presents the select proceedings the 2nd International Conference on Mechanical and Energy Technologies (ICMET 2021). The broad range of topics and issues covered are bulk deformation processes and sheet metal forming, composites, ceramics, and polymers processing, corrosion, heat treatment, microstructure and materials properties, energy materials, failure and fracture mechanics, friction, wear, tribology, and surface engineering, functionally graded materials, cellular materials, low friction and corrosion resistive materials for energy applications, lubricants and lubrication, machinability and formability of materials, material science and engineering, and materials for energy storage. This book will be useful for students, researchers, and professionals working in the areas of mechanical and industrial engineering, energy technologies, and allied fields.